2022
DOI: 10.3389/fepid.2022.876706
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnic, and Sex Differences in Prevalence of and Trends in Hallucinogen Consumption Among Lifetime Users in the United States Between 2015 and 2019

Abstract: BackgroundThe current study is one of the first to examine race, ethnic, and sex differences in the prevalence of and trends in hallucinogen use among lifetime users in the United States.MethodsData came from the 2015–2019 National Survey on Drug Use and Health and included respondent's reporting ever-using hallucinogens (n = 41,060; female = 40.4%). Descriptive and multinomial logistic regression analyses were conducted in Stata.ResultsHighest prevalence of past year hallucinogen use was among Asian females (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Compared with individuals identifying as White, those identifying as Asian, Black, or multiracial were more likely to report past-year ecstasy/MDMA use. Similar demographic findings were reported by Davis et al 25 in relation to past-year hallucinogen use. However, our findings are in contrast to older epidemiologic research, in which those identifying as Black were actually less likely to use ecstasy/MDMA.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Compared with individuals identifying as White, those identifying as Asian, Black, or multiracial were more likely to report past-year ecstasy/MDMA use. Similar demographic findings were reported by Davis et al 25 in relation to past-year hallucinogen use. However, our findings are in contrast to older epidemiologic research, in which those identifying as Black were actually less likely to use ecstasy/MDMA.…”
Section: Discussionsupporting
confidence: 89%
“…[31][32][33] However, more recent research has shown that this is not the case. 25,34 Some studies suggest that factors including trauma from resettlement, acculturation, urbanicity, and cultural influences may explain the increasing substance use seen in both Asian and Black populations. 21,[35][36][37] These data suggest that ecstasy/ MDMA use patterns are heterogeneous by racial and ethnic subgroups and different from prior epidemiological studies of ecstasy/MDMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our sample was predominantly white, young and educated, and although this appears to partly reflect the common demographic profile of psychedelic users ( Yockey et al, 2020 ), GDS may also disproportionately reach these populations ( Barratt et al, 2017 ). Low representation of ethnic minorities and socioeconomically disadvantaged individuals is a significant problem in psychedelic research, especially considering these populations are greatly affected by the mental conditions that any future psychedelic therapy would be used to treat ( Ortiz et al, 2022 ; Rea and Wallace, 2021 ; Williams et al, 2021 ); and recent evidence does suggest the psychedelic user population is becoming increasingly ethnically diverse ( Davis et al, 2022 ). Furthermore, those reached by the survey advertising and who choose to volunteer may have specific interests and knowledge about the topics of the survey ( Eysenbach and Wyatt, 2002 ); and for instance be better educated about optimal practices of psychedelic use, contributing to more favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%